Systematic Review Tentang Inovasi Daerah Kalimantan Timur (Studi Berdasarkan Scopus Database) - Ahmad Hudaifah (Nusantara Innovation Journal, 2025)
Innovation is an indicator of the quality of human resources in a region. East Kalimantan Province as one of the administrative areas intends to improve the quality of innovation and human resources is trying its best steps such as strengthening the ecosystem and real programs for regional innovation. This study aims to produce an innovation mapping in East Kalimantan using the Scopus database. The methodology used is a systematic review with qualitative content analysis. This paper analyses 37 selected articles in English on Scopus. The results of the study concluded that all articles with the keyword Innovation can be classified into 5 groups including (1) archaeology and culture, (2) biology, agriculture and environment, (3) economics and business, (4) mining and earth sciences, (5) social sciences and law. The tendency of innovation has developed into various sectors although in limited numbers. This conclusion is supported by the Vos Viewer output which produces 12 groups of words with a minimum frequency of occurrence of 3 times in the Scopus database, including language and culture, social responsibility, material waste management, organizational governance, urban area development, and so on.